2019
DOI: 10.1063/1.5079964
|View full text |Cite
|
Sign up to set email alerts
|

Spin properties of single-molecule magnet of double-decker Tb(III)-phthalocyanine (TbPc2) on ferromagnetic Co film characterized by spin polarized STM (SP-STM)

Abstract: We demonstrate a direct visualization of the magnetic hysteresis of a single-molecule magnet bis(phthalocyaninato)terbium(III) (TbPc2) adsorbed on the Co islands, which covers a submonolayer region of an Au(111) surface by utilizing the spin-polarized scanning tunneling microscope (SP-STM) and monitoring the magnetotunneling resistance. We found that the TbPc2 molecule is spin polarized and attached to the ferromagnetic Co islands. The result of the SP-STM measurements showed that the spin of TbPc2 is antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The height is similar to what we observed for the second layer of TbPc 2 on the Ag(111) surface. 37 The horizontal direction of the image is aligned along the [1−10] direction of the Au(111) surface. In order to observe the detail of the bonding configuration of the second layer molecule, we show the image obtained with the small gap voltage of −100 mV in Figure 4b.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The height is similar to what we observed for the second layer of TbPc 2 on the Ag(111) surface. 37 The horizontal direction of the image is aligned along the [1−10] direction of the Au(111) surface. In order to observe the detail of the bonding configuration of the second layer molecule, we show the image obtained with the small gap voltage of −100 mV in Figure 4b.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The processing of single-molecule magnets (SMMs) into films with variable thickness, down to monolayers or sub-monolayers [1,2], is motivated by the perspective use of these magnetically bistable materials in spintronic devices [3] or as individually addressable, surface-supported magnetic bits [4]. A major breakthrough in the field was the recent discovery that some organometallic monodysprosium(III) SMMs retain a memory effect above the normal boiling point of liquid dinitrogen [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the magnetic hysteresis exhibits no gap, which is similar to paramagnetic materials. It has been shown that QTM can be significantly reduced by immobilizing SMMs onto carbon nanotubes or a MgO substrate, or the adsorption on Co bilayer islands formed on the Au(111) surface …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that QTM can be significantly reduced by immobilizing SMMs onto carbon nanotubes 16−18 or a MgO substrate, 19 or the adsorption on Co bilayer islands formed on the Au(111) surface. 20 Metal phthalocyanines (MPcs), commonly used as dyes and pigments, are supposedly the best candidates for deposition of thin films under ultrahigh vacuum conditions because of (i) their ideal thermal and chemical stability when used in the molecular beam techniques and (ii) the tendency to grow in ordered phases. 21 Technological potential of MPc is impressive and spans over a variety of applications, such as chemical sensors, 22 intrinsic semiconductors, 21 field-effect transistors, 23 T h i s c o n t e n t i s organic light-emitting diodes, 24 single-molecule devices, 25 photovoltaic cells, 26 and materials for nonlinear optics or laser recording.…”
Section: ■ Introductionmentioning
confidence: 99%